Analisis Pengaruh Rasio Keuangan Terhadap Harga Saham Perusahaan Pada Sub Sektor Sektor Perdagangan Besar (Barang Produksi Dan Barang Konsumsi) Yang Tercatat Di BEI Tahun 2019-2020 - Anggun Pertiwi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to find out if there is an influence of the financial ratio of NPM, ROI, ROE and DER to the stock price. During the development of covid-19 cases some companies experience a decrease in terms of corporate pro forma and as investors also need to consider again about the continuation of a company by looking at the financial ratio of a company. This research was conducted on companies listed on the Indonesia Stock Exchange in large trade sub-sectors (production and consumption goods) in 2019-2020. In this study, samples used purposive sampling methods with certain actateria. In this study, breganda analysis tests because they have more than one indepdnden variable. In this study it has been proven that only NPM variables (net profit margin) have an effect on stock prices. Keywords : Net Profit Margin ( NPM ), Return On Investment ( ROI ), Return On Equity ( ROE ) dan Debt to Equity Ratio ( DER)